2018
DOI: 10.3390/atmos9090351
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Outdoor Particles (PM2.5) and Associated Child Morbidity and Mortality in Socially Deprived Neighborhoods of Nairobi, Kenya

Abstract: Exposure to air pollution is associated with adverse health outcomes. However, the health burden related to ambient outdoor air pollution in sub-Saharan Africa remains unclear. This study examined the relationship between exposure to outdoor air pollution and child health in urban slums of Nairobi, Kenya. We conducted a semi-ecological study among children under 5 years of age from two slum areas and exposure measurements of particulate matter (PM2.5) at the village level were aligned to data from a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
(54 reference statements)
1
28
0
Order By: Relevance
“…The adverse effects of PM 2.5 on the respiratory-cardiovascular system have been repeatedly confirmed [1][2][3][4][5][6][7][8][9][10][11][12]. Epidemiologic studies that assess exposure risk to different ambient PM 2.5 concentration levels have relied on the U.S. Environmental Protection Agency's (EPA) network of ground-based ambient air pollutant monitors [4,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effects of PM 2.5 on the respiratory-cardiovascular system have been repeatedly confirmed [1][2][3][4][5][6][7][8][9][10][11][12]. Epidemiologic studies that assess exposure risk to different ambient PM 2.5 concentration levels have relied on the U.S. Environmental Protection Agency's (EPA) network of ground-based ambient air pollutant monitors [4,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Each column displays total observations (n) and percent (%) for emergency department (ED)/inpatient (IP) asthma case-control groups 2. Significance was evaluated with the Chi Square test: * = p ≤ 0.05; † = p ≤ 0.01 3. Significant age group differences between ED asthma cases and IP asthma cases, p ≤ 0.01 4.…”
mentioning
confidence: 99%
“…Another approach is to consider existing death tolls from related causes. As a cause of death, AGW will hardly be inseparable from poverty, which is also linked to air pollution (Egondi et al, 2018). Outdoor air pollution (mostly by PM2.5) is now causing 3 × 10 6 premature deaths per year, mainly in Asia; in a business-as-usual scenario, this figure could double by 2050 (Lelieveld et al, 2015).…”
Section: Best-case Estimatementioning
confidence: 99%
“…PM 2.5 pollution remains an under-recognized environmental health risk in such countries [ 18 ]. Applying logistic and Poisson regression models, Egondi et al [ 20 ] found that exposure to high levels of PM 2.5 pollution is associated with a high risk for childhood morbidity and a high children mortality rate in Nairobi, Kenya. Using cross-country level data of Africa from 2000 to 2015, Owili et al [ 21 ] provided the evidence that there exists a significant relationship between PM 2.5 and under-five and maternal mortality in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Since the epithelial linings of children’s lungs and immune systems are not fully developed, children are more vulnerable to ambient air pollution compared to adults [ 20 , 27 , 28 ]. This paper focuses on evaluating the impacts of fine particulate air pollution on U5MR, as well as explores the role of public service in moderating the PM 2.5 -mortality relationship with panel data of 94 countries over the period 1998–2014.…”
Section: Introductionmentioning
confidence: 99%